Development of novel genetic cancer vaccines based on membrane‐attached β2 microglobulin. (6th February 2013) - Cafri, Gal; Margalit, Alon; Tzehoval, Esther; Eisenbach, Lea; Gross, Gideon
Abstract : Cytotoxic T lymphocytes (CTLs) are the major effector arm of the immune system against tumors. Many tumor‐associated antigens (TAAs), known today as potential rejection antigens, were identified by their ability to induce CTL responses. CTLs utilize their clonotypic T cell receptor (TCR) to recognize short antigenic peptides presented on major histocompatibility complex (MHC)‐I proteins. These consist of a membrane‐attached α heavy chain, which forms the peptide binding pocket, and a noncovalently associated β2 m light chain, not anchored to the cell membrane. CTL activation requires that antigenic peptides be presented initially on professional antigen presenting cells (APCs), primarily dendritic cells (DCs). Autologous DCs are a powerful tool for the induction of antitumor responses and are thus widely explored as vehicles for cancer vaccines. Although encouraging evidence for the induction of tumor‐specific CTLs by ex vivo –manipulated DCs came from numerous animal studies, reproducible objective clinical response in human trials is yet to be demonstrated.